Impact of pre-stenting antiplatelet therapy regimens on clinical outcomes following carotid artery stenting: a retrospective analysis - Arslanturk, Oguz; Gel, Mehmet Selim; Keskin, Emrah (The European Research Journal, 2025)
Objective: This study investigates the influence of various antiplatelet regimens before carotid artery stenting (CAS) on short-term and long-term clinical outcomes. Effective antiplatelet therapy is vital for enhancing the success and safety of CAS. Determining the best approach remains a priority. Methods: This retrospective cohort analysis involved 235 patients who underwent CAS at a single institution between October 2020 and October 2024. Participants were divided into three groups based on the antiplatelet regimen administered before the procedure: dual antiplatelet therapy (DAPT), aspirin monotherapy (SAPT-A), and clopidogrel monotherapy (SAPT-C). The main outcomes evaluated were stroke, transient ischemic attack (TIA), and bleeding complications. Secondary outcomes included restenosis, stent thrombosis, and death. Statistical methods were applied to compare outcomes across the groups. Results: Stroke (0.8%) and TIA (2.5%) were notably less frequent in the DAPT group compared to the SAPT-A (7.1% and 12.5%, respectively) and SAPT-C (6.9% and 8.6%, respectively) groups (P<0.05). Rates of stent thrombosis (1.7%-1.8%) and mortality (0.8%-3.4%) at six months showed no significant differences among the groups (P>0.05). Conclusions: Pre-procedural DAPT reduces short-term ischemic complications in CAS. However, long-term outcomes were comparable across regimens. These findings suggest that antiplatelet strategies should be individualized. Larger studies with longer follow-ups are needed.